DAMPAK PEMBELAJARAN KOOPERATIF TIPE STAD TERHADAP HASIL BELAJAR BIOLOGI SISWA SMPN 3 BATANG ANAI PARIAMAN - Gustina Indriati; Evrialiani Rosba; Tyara Jayus Mely (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2018)
The purpose of this research is to figure out the effect of cooperative strategy type STAD with LDS on the students’ cognitive domain learning outcomes in Biology class, at the eighth grade of SMPN 3 Batang Anai. The research was an experimental research with Randomised Control Group Postest Only Design. The research instrument was a multiple choice test consisting of 55 test items. The cognitive test result of the experimental group was 70.46, whereas that of the control group was 60.07. T test result shows tcount (3.34) > ttable (1.68). Thus the hypothesis was accepted. It is concluded that the cooperative learning Type STAD with LDS gives an effect on the students’ cognitive domain learning outcomes of Biology subject taught to the eighth grads students of SMPN 3 Batang Anai Padang Pariaman regency.